The Influence of Teacher Asking Skills on Student Learning Outcomes in Class VII B PAI Subjects at SMP Al-Amaanah Matesih Karanganyar - Faujiah, Ika Alfin; Isfihani, Isfihani; Praptiningsih, Praptiningsih (Edumaspul: Jurnal Pendidikan, 2023)
This study aims to find out how much influence the skills of asking questions to the teacher have on student learning outcomes in PAI class VIIB SMP Al-Amaanah Matesih Karanganyar for the 2022/2023 academic year. This research uses a descriptive quantitative method. The population in this study were students of class VIIB SMP Al-Amaanah Matesih Karanganyar. The sampling technique used in this study was simple random sampling. The sample used was 32 students. The prerequisite test calculations in this study used the normality test with a sig. 0.05. Based on the data from the Kolmogorof-Smirnov test, it is known that the asymp sig. (2-tailed) significance value is 0.123 > 0.05, meaning that the residual values are normally distributed. The data analysis method used is simple linear regression analysis with an error rate of 5%. Regression coefficients were obtained for components a = 22.49, and b = 0.249. Then it can be obtained regression Y = 22.49 + 0.249X so that it is known that a positive value at a constant of 22.49 indicates that the teacher’s questioning skills have a positive influence on student learning outcomes. The questioning skill teacher at SMP Al-Amaanah Matesih Karanganyar obtained a score of 62.5% with a total of 23 respondents, this shows that the teacher’s skill ability is in a moderate position. The value of the coefficient of determination (R-square) is 0.139 or 13.9%. This means that the magnitude of the influence of the teacher’s questioning skills on student learning outcomes is only 13.9%, the rest is influenced by other factors. Based on the calculation results of the product-moment correlation analysis, the results obtained are recounted 0.373 > table 0.349 so Ho is rejected and Ha is accepted, it is stated that there is an influence of the teacher’s questioning skills on student learning outcomes.